2016
DOI: 10.1155/2016/3181676
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Presentation of a Male with Oral-Facial-Digital Syndrome Type 1 Related Ciliopathy

Abstract: Background. Oral-facial-digital syndrome type 1 (OFD1) is a rare condition with X-linked dominant inheritance caused by mutations in the Cxorf5 (OFD1) gene. This gene encodes the OFD1 protein located within centrosomes and basal bodies of primary cilia. Approximately 15–50% of patients with OFD1 progress to end-stage kidney disease following development of polycystic changes within the kidneys. This condition almost always causes intrauterine lethality in males. Description of Case Diagnosis and Treatment. A C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Sharma et al reported an atypical presentation of OFD1 mutation in a male patient without the classical OFD1 phenotype. This patient presented ESRD without any evidence of polycystic kidney disease [16]. The spectrum of OFD1 mutations in males reported previously is summarized in Table 1.…”
Section: Discussionmentioning
confidence: 78%
“…Sharma et al reported an atypical presentation of OFD1 mutation in a male patient without the classical OFD1 phenotype. This patient presented ESRD without any evidence of polycystic kidney disease [16]. The spectrum of OFD1 mutations in males reported previously is summarized in Table 1.…”
Section: Discussionmentioning
confidence: 78%
“…OFD1 variants have previously been reported in association with inherited renal cystic disease, with hypertension ( 22 ). Sharma et al described an XY male with a partial deletion of the OFD1 gene associated with hypogonadism ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of autosomal dominant polycystic kidney disease (ADPKD), cysts in OFDS I originate from glomeruli rather than renal tubules. Additionally, size of cysts are not so large and overall renal size is not enlarged as in ADPKD (2). Renal insufficiency has been reported in OFDS primarily due to polycystic kidney disease.…”
Section: Discussionmentioning
confidence: 97%
“…Two of those types (OFDS I and OFDS IV) are associated with miscellaneous phenotypes and organ involvements that could overlap with each other in some presentations. OFDS type I is the most frequent type with estimated incidence of 1:50 000 -1:250 000 live births (2). It may occur in 1.5:1000 patients with cleft lip, cleft palate or both.…”
Section: Discussionmentioning
confidence: 99%